PEMODELAN BANJIR DI SUB DAERAH ALIRAN SUNGAI BANJIR KANAL TIMUR KOTA SEMARANG - Aprianto, Widhi Kurniawan; Sanjoto, Tjaturahono Budi; Tjahjono, Heri (Geo-Image, 2019)
The increased frequency of floods that occurred in the East Flood Canal should be done prediction to reduce losses.With that case this study aims 1) To knowing the result of flood modelsin the East Flood Canal Sub Watersheed on 2, 5, 10, 25, 50, 100 and 200 years periodically. 2) Identify flood-prone areasbased on modelsin the East Flood Canal Sub Watersheed in Semarang City.The research used quantitative research methods, with the population is area in East Flood Canal Sub Watersheed. The analysis technique which was used unsteady-flow and HSS-SCS. In this study showed that main river of East Flood Canal Sub Watersheed has overflowed on 2 years up to 200 years periodically with a peak discharge volime 202,32 m3/sec in a 2 year periodically and 283,15 m3/sec in a 200 year periodically. Unsteady flow simulation showed that overflowed East Flood Canal occured in 8 Villages along the main river. The largest flood-prone area on Terboyo Kulon Village with 112 Ha distribution and followed by Tanjung Mas Village 107 Ha, due to tidal.